The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000516575
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Severity of Moral Distress in Nephrology Fellows: A National Survey

Abstract: <b><i>Introduction:</i></b> Moral distress is a negative affective response to a situation in which one is compelled to act in a way that conflicts with one’s values. Little is known about the workplace scenarios that elicit moral distress in nephrology fellows. <b><i>Methods:</i></b> We sent a moral distress survey to 148 nephrology fellowship directors with a request to forward it to their fellows. Using a 5-point (0–4) scale, fellows rated both the frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Racial or ethnic categories reflected the study contexts. A USA study, while seemingly adapting categories used to collect federal data, differentiated between “White” and “Middle Eastern or North African” (Saeed et al., 2021); categories which would be grouped together in official data (US Office of Management and Budget, 1997). The “White” racial category was seemingly used to mean people of European ancestry, with Morley, Bradbury‐Jones, et al.…”
Section: Resultsmentioning
confidence: 99%
“…Racial or ethnic categories reflected the study contexts. A USA study, while seemingly adapting categories used to collect federal data, differentiated between “White” and “Middle Eastern or North African” (Saeed et al., 2021); categories which would be grouped together in official data (US Office of Management and Budget, 1997). The “White” racial category was seemingly used to mean people of European ancestry, with Morley, Bradbury‐Jones, et al.…”
Section: Resultsmentioning
confidence: 99%
“… 53 A recent American survey of 142 nephrology fellows showed that 81% of respondents experienced moral distress related to starting dialysis in futile circumstances and 75% experienced moral distress when continuing dialysis on hopelessly ill patients. 54 Therefore, more education, training, and support is urgently needed for clinicians to prevent moral distress resulting from compromised end-of-life care experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Dies spüren Mitglieder des Pflegeteams ebenso wie Ärzt*innen. Saeed et al untersuchten Häufigkeit, Ausmaß und Ursachen von Moral Distress von angehenden Fachärzt*innen für Nephrologie [23]. Die Interaktion mit An-und Zugehörigen wurde von 76 % der Befragten mit einem hohen Stresslevel assoziiert.…”
Section: Originalarbeitunclassified